Mineralogical Investigations of Wall Accretion and Lining of the Blast Furnace Hearth - A. Makavetskas (International Mineral Processing Congress, 2018)
"The purpose of the research is to study the mineralogical features of the structure of the wall accretion formed during melting on the working surface of the walls of metallurgical aggregates and adversely affect the stability of the lining of blast furnaces (BF). We presented the results of studies of the material composition of lining and wall accretion of the furnaces of blast furnaces of the metallurgical plant specializing in the smelting of ferromanganese, nodular and pig iron. It is established that the garnissage is an aggregate of layered texture, formed as a result of the crystallization of slag and metallic melts. Refractory calcium and magnesium silicates and aluminosilicates (minerals of the melilite group, leicite, olivine group minerals) and amorphous glassy oxide solid solutions of variable composition crystallize from the slag melts in the upper part of the hearth. In the slag matrix, inclusions of carbon (amorphous and graphite) and products of crystallization of metallic melts of alpha-iron, iron carbides and / or manganese are observed. Evidence of carbon evolution (in the form of graphite) is precisely in the crystallization of metal melts, there are significant differences in the structure of carbon in coke and in the garnissage. The conducted studies confirm that it is impossible to obtain reliable information on the material composition of new formations in the blast-furnace process without using a complex of modern methods of technological mineralogy.INTRODUCTION The formation of the wall accretion (garnissage) - a solid protective layer as a result of smelting products crystallization on the inner (working) surface of the liner. This is due to the design of blast furnaces with a high-efficiency heat sink using copper coolers and the use of carbon blocks with high thermal conductivity in the lining. The objective of the study was research of the material composition of the lining and wall accretion of the blast furnace hearth of one metallurgical plant that specialized in smelting ferromanganese, nodular and pig iron, to assess the effect of new formations for stability of the lining of blast furnaces (BF)."